Relationship between customer satisfaction and loyalty towards ASNB services in Kuala Lumpur / Siti Nazirah Omar - Omar, Siti Nazirah (Faculty of Business and Management, 2006)
Nowadays, unit trust is one of the investments involving the consumers. There are so many competitors in the industry especially from the bank institutions. In this regard, ASNB has a crucial and challenging task in monitoring as well as measuring customer satisfaction and loyalty towards its services performance. Therefore, the objectives of this study are to ascertain the investors' level of satisfaction and loyalty towards ASNB services and to determine the relationship between the two variables. The researcher has used the cognitive (perception) and affective (feeling) components to measure the investors level of satisfaction. There are four service marketing variables (services and service product, people, physical evidence and process) under the cognitive component. , Besides, two attributes that measured loyalty are repurchasing intention and recommending to others.